Deep winter convection and phytoplankton dynamics in the NW Mediterranean Sea under present climate and future (horizon 2030) scenarios - Macias, Diego (Sci Rep, 2018)
Deep water convection (DC) in winter is one of the major processes driving open-ocean primary productivity in the Northwestern Mediterranean Sea. DC is highly variable in time, depending on the specific conditions (stratification, circulation and ocean-atmosphere interactions) of each specific winter. This variability also drives the interannual oscillations of open-ocean primary productivity in this important region for many commercially-important fish species. We use a coupled model system to 1) understand to what extent DC impacts phytoplankton seasonality in the present-day and 2) to explore potential changes in future scenarios (~2030). Our model represents quite accurately the present-day characteristics of DC and its importance for open-ocean phytoplankton blooms. However, for the future scenarios the importance of deep nutrients in fertilizing the euphotic layer of the NW Mediterranean decreases. The model simulates changes in surface density and on the levels of kinetic energy that make mesoscale activity associated with horizontal currents to become a more important fertilization mechanism, inducing subsequently phenological changes in seasonal plankton cycles. Because of our focus on the open-sea, an exact quantification of the impact of those changes on the overall biological production of the NW Mediterranean cannot be made at the moment.